Analysis of the Influence of Workload and Work Environment on Employee Turnover at PT. XYZ - Teguh Setiawan Wibowo; Pandu Adi Cakranegara; I Gusti Ngurah Agung Dewantara Putra; Eka Kurnia Saputra; Mekar Meilisa Amalia (Quantitative Economics and Management Studies, 2022)
The purpose of this study was to analyze the influence of workload and work environment on employee turnover at PT. XYZ. The research design used in this study used quantitative associative methods. Based on the results of data analysis that has been carried out in the first hypothesis (H1), the value of t count > t table is 11,892 > 1,678 and in the second hypothesis (H2) the value of t count > t table is 13,968 > 1,678 which means that the workload and work environment has a positive and significant effect on employee turnover at PT. XYZ while the R-square value obtained is 0.869 which states that the workload and work environment variables affect employee turnover at PT. XYZ is 86.90% and the remaining 13.10% is influenced by other variables.